Research on antibiotic resistance in Helicobacter pylori: a bibliometric analysis of the past decade - Yuan, Chengzhi; Yu, Chang; Sun, Qifang; Xiong, Meng; Zhou, Sainan; Zeng, Meiyan; Song, Houpan (Frontiers in Microbiology, 2023)
Resistance of Helicobacter pylori (H. pylori) to antibiotics has reached alarming levels worldwide, and the efficacy of the H. pylori eradication treatment has decreased dramatically because of antibiotic resistance. To gain a more comprehensive understanding of the development status, research hotspots, and future trends related to H. pylori antibiotic resistance, we conducted a thorough retrospective analysis via the bibliometrics method. We searched the Science Citation Index Expanded of the Web of Science Core Collection for all pertinent articles on H. pylori antibiotic resistance from 2013 to 2022. R-bibliometrix, CiteSpace, and VOSviewer tools were utilized to depict statistical evaluations in order to provide an unbiased presentation and forecasts in the field. We incorporated a total of 3,509 articles related to H. pylori antibiotic resistance. Publications were inconsistent prior to 2017, but steadily increased after 2017. China generated the most papers and the United States of America received the most citations and the highest H-index. Baylor College of Medicine was the most influential institution in this field, with the highest number of publications and citations, as well as the highest H-index. Helicobacter was the most productive journal, followed by the World Journal of Gastroenterology and Frontiers in Microbiology. The World Journal of Gastroenterology had the highest citation. Graham, David Y was the most productive and cited author. Clarithromycin resistance, prevalence, gastric cancer, quadruple therapy, sequential therapy, 23S rRNA, whole genome sequencing, bismuth, and probiotics appeared with a high frequency in the keywords. The top keywords with the highest citation bursts were vonoprazan, RdxA, biofilm formation, and fatty acid chain. Our research illustrated a multi-dimensional facet and a holistic knowledge structure for H. pylori antibiotic resistance research over the past decade, which can serve as a guide for the H. pylori research community to conduct in-depth investigations in the future.